Perceived barriers, facilitators, and needs to the current use of an EMR system among pharmacists in a tertiary hospital a qualitative study - Barsatan, Giullian Karloz T.; Namata Sam Francis Lorenz I.
The Computerized Registry on Admissions and Discharges (RADISH) is an electronic medical record (EMR) system that has been implemented in the University of the Philippines-Philippine General Hospital (UP-PGH), a tertiary hospital in the Philippines since 2020. Its purpose is to streamline medical records in the provision of patient care, an area where clinical and dispensing pharmacists are involved in. However, despite this purpose, the functions of clinical and dispensing pharmacists are not sufficiently integrated into RADISH. This study aimed to describe how clinical and dispensing pharmacists use RADISH, describe their perceived barriers, facilitators, and needs related to their use, and to formulate potential interventions in order to address emergent needs. Following purposive sampling, ten (10) clinical and ten (10) dispensing pharmacists were interviewed using a semi-structured format. Resulting narratives on their use, experience, and preparedness were identified inductively — with their EMR use presented into a thematic map. Their perceived barriers, facilitators, and needs were thematically analyzed through the Capability, Opportunity, Motivation-Behavior (COM-B) and Theoretical Domains Framework (TDF). Clinical pharmacists use the EMR system mostly in accessing patient charts, while dispensing pharmacists mainly use the system for verification and medication approvals prior to dispensing. Among clinical and dispensing pharmacists, the most common theme for perceived barriers is due to the lack of training and resources; for facilitators, workflow improvements; and for needs, interface and system design improvement. In relation to such, interventions recommended are: 1) to provide features that pharmacists request, such as automatic saving of drafts, interface for transition of medicines, tagging features for emergency cases, etc; 2) capacity building The Computerized Registry on Admissions and Discharges (RADISH) is an electronic medical record (EMR) system that has been implemented in the University of the Philippines-Philippine General Hospital (UP-PGH), a tertiary hospital in the Philippines since 2020. Its purpose is to streamline medical records in the provision of patient care, an area where clinical and dispensing pharmacists are involved in. However, despite this purpose, the functions of clinical and dispensing pharmacists are not sufficiently integrated into RADISH. This study aimed to describe how clinical and dispensing pharmacists use RADISH, describe their perceived barriers, facilitators, and needs related to their use, and to formulate potential interventions in order to address emergent needs. Following purposive sampling, ten (10) clinical and ten (10) dispensing pharmacists were interviewed using a semi-structured format. Resulting narratives on their use, experience, and preparedness were identified inductively — with their EMR use presented into a thematic map. Their perceived barriers, facilitators, and needs were thematically analyzed through the Capability, Opportunity, Motivation-Behavior (COM-B) and Theoretical Domains Framework (TDF). Clinical pharmacists use the EMR system mostly in accessing patient charts, while dispensing pharmacists mainly use the system for verification and medication approvals prior to dispensing. Among clinical and dispensing pharmacists, the most common theme for perceived barriers is due to the lack of training and resources; for facilitators, workflow improvements; and for needs, interface and system design improvement. In relation to such, interventions recommended are: 1) to provide features that pharmacists request, such as automatic saving of drafts, interface for transition of medicines, tagging features for emergency cases, etc; 2) capacity building among pharmacists through training; 3) interprofessional support, such as incorporating telepharmacy counseling referral through RADISH in the medicine clinics’ procedure; among others. The EMR system is found to be essential to the role of clinical and dispensing pharmacists with positive overall perception, having some shortcomings identified. The implementation and ongoing development of the EMR should take into account pharmacist perspectives not only to address barriers, but also to support the profession towards the shared goal of complete and quality patient care.